-3(4x-13)=-(4x+17)

Simple and best practice solution for -3(4x-13)=-(4x+17) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(4x-13)=-(4x+17) equation:



-3(4x-13)=-(4x+17)
We move all terms to the left:
-3(4x-13)-(-(4x+17))=0
We multiply parentheses
-12x-(-(4x+17))+39=0
We calculate terms in parentheses: -(-(4x+17)), so:
-(4x+17)
We get rid of parentheses
-4x-17
Back to the equation:
-(-4x-17)
We get rid of parentheses
-12x+4x+17+39=0
We add all the numbers together, and all the variables
-8x+56=0
We move all terms containing x to the left, all other terms to the right
-8x=-56
x=-56/-8
x=+7

See similar equations:

| 10•x=3/2 | | (x^2−x−68)^(4/3)=256 | | .5+.25(x+16)=4+.75x | | 20-5k=-10k | | −​4/1a−4=​4/7​​a−3 | | -17=1-2+3x | | f/2-12=8 | | 2.2x+4.4=0 | | 7s-0=4s | | b/9+1/5=19 | | 3-(5x-4)=12 | | 7*5*n= | | x+(12/100)x=17.92 | | 7+w/2=4 | | 8x=3x=15 | | 11x+47=24 | | 10x+11=19+5x+9x | | 33=42+2x-16 | | 5(x-2)+6=4(x+1) | | 4x=(-5x+58)/6 | | 6x2+1=13 | | 3x-31+2x+1=180 | | 15b+5=16b | | 7-3x-1=-3x | | 612=x421 | | a/4+8=10 | | 5b+4b=9b | | 10-(9g+1)=-9 | | 3x(2+11x)= | | 15b-5b=10b | | r-10=-10-r | | 0.2(d–8)=0.3d+7–5+0.5d |

Equations solver categories